Meta-Analysis Study: The Influence of Motivation on Teacher Performance in Indonesia - Muflihan, Yenni; Prasetyaningtyas, Wulansari; Fajri, Nur; Sari, Nurmala (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is to examine the relationship between motivation and teacher performance in Indonesia. Researchers synthesize the results of 47 research studies that have met the criteria and find out the overall relationship of teacher motivation and performance. The data analysis technique used is a quantitative meta-analysis approach with correlation analysis, and the analysis using JASP Application. Based on the results of the study, it can be concluded that the average of the Effect size is 0.811. This value exceeds the standard value included in the high category that is 0.5. Therefore, the results of this study prove that motivation has a strong relationship with teacher performance.